Experimental and numerical investigation the effect of concrete strength and area of steel reinforcement on mechanical performance of functionally graded reinforced concrete beams (Fracture and Structural Integrity, 2023)
In this work, an experimental and numerical program was designed to evaluate the role of compressive strength, Fc, and area of reinforcing steel, As, on the flexural behavior of functionally graded reinforced concrete beams. Eighteen layered sections of reinforced concrete beams were tested with different compressive strengths arrangement and area of main steel. The result showed that the minimum steel reinforcement with higher compressive strength in the compression zone increases load capacity and ductility. The average steel reinforcement with higher strength in the compression zone increases load capacity and decreases ductility. The results also approved that; higher strength in the compression zone can be used in beams with a high tensile steel ratio for decreasing compression steel as an economic side. 3D finite element was executed using ABAQUS to simulate experimental beams. The numerical result showed variation from the experimental but still, the behavior of numerical beams is the same as the experimental.
Keywords: Compressive strength; area of steel; 3D finite element; functionally graded